2013
DOI: 10.5173/ceju.2013.03.art5
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular invasion in testicular germ cell tumors: clinicopathological correlates

Abstract: IntroductionWe assessed clinical–pathological correlates of lymphovascular invasion in testicular germ–cell tumors.Material and methodsArchived pathology specimens from 145 patients treated by radical orchiectomy for testicular germ cell tumors at our institution in 1995–2006 were reanalyzed by a dedicated urologic pathologist, and the corresponding medical records were reviewed. The association of lymphovascular invasion with clinical and pathological parameters was tested using stepwise logistic regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Remarkably, elevation of HCG significantly associated with vascular invasion and it also significantly impacted relapse-free survival, even when adjusting for vascular invasion effect. It has been suggested that HCG elevations in testicular germ cell tumors (both seminomas and non-seminomas) positively regulate the vascular endothelial growth factor (VEGF), leading to vessel neoformation, which explains both the association with vascular invasion status and the poor prognostic value of this finding [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, elevation of HCG significantly associated with vascular invasion and it also significantly impacted relapse-free survival, even when adjusting for vascular invasion effect. It has been suggested that HCG elevations in testicular germ cell tumors (both seminomas and non-seminomas) positively regulate the vascular endothelial growth factor (VEGF), leading to vessel neoformation, which explains both the association with vascular invasion status and the poor prognostic value of this finding [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Yossepowitch et al analyzed 145 patients with testicular germ cell tumors who had undergone radical orchiectomy [ 6 ]. Lymphovascular invasion was detected in 38 (26%) men and was significantly correlated with younger age, testicular pain at presentation, elevated pre–orchiectomy serum tumor markers, nonseminoma histology, and advanced clinical stage.…”
mentioning
confidence: 99%